Diagnosis of benign notochordal cell tumor of the spine: is a biopsy necessary?. Issue 1 (24th November 2017) - Tateda, Satoshi; Hashimoto, Ko; Aizawa, Toshimi; Kanno, Haruo; Hitachi, Shin; Itoi, Eiji; Ozawa, Hiroshi
Key Clinical Message: Benign notochordal cell tumor is a benign intraosseous lesion, demonstrates characteristic imaging features. The lesion demonstrates low‐signal intensity in T1‐weighted images, high‐signal intensity in T2‐weighted images, and no enhancement with contrast medium in MRI and slight osteosclerosis in CT. If typical imaging findings are identified, biopsy is not necessary. Abstract : Benign notochordal cell tumor is a benign intraosseous lesion, demonstrates characteristic imaging features. The lesion demonstrates low‐signal intensity in T1‐weighted images, high‐signal intensity in T2‐weighted images, and no enhancement with contrast medium in MRI and slight osteosclerosis in CT. If typical imaging findings are identified, biopsy is not necessary.